2011
DOI: 10.1159/000323351
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of Skin Cytokine Secretion by House Dust Mite Extracts

Abstract: Background: Skin contact with house dust mites may contribute to atopic dermatitis and other skin diseases. We sought to determine if molecules from house dust mites could influence the release of proinflammatory cytokines and chemokines from epidermal keratinocytes and dermal fibroblasts grown in a human skin equivalent (HSE) model. Methods: HSEs consisting of an epidermis of keratinocytes with stratum corneum over a dermis of fibroblasts in a collagen matrix were challenged with Dermatophagoides farinae, D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 67 publications
(49 reference statements)
1
20
0
4
Order By: Relevance
“…A number of studies have shown that house dust mite extracts contain molecules that can induce responses from cells of the skin and bronchial epithelium of the lungs and these may influence the manifestation of inflammation and the course of allergic reactions in the skin and bronchial airway (Arlian et al 2008, 2009a; Arlian & Morgan 2011; Boasen et al 2005; Chen et al 2003; King et al 1998; Lee et al 2008; Machado et al 1996; Sohn et al 2007; Tomee et al 1998; Wong et al 2006). Most of the lung studies have challenged epithelial cells with specific allergens (mostly group 1) or whole extract of D. pteronyssinus .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that house dust mite extracts contain molecules that can induce responses from cells of the skin and bronchial epithelium of the lungs and these may influence the manifestation of inflammation and the course of allergic reactions in the skin and bronchial airway (Arlian et al 2008, 2009a; Arlian & Morgan 2011; Boasen et al 2005; Chen et al 2003; King et al 1998; Lee et al 2008; Machado et al 1996; Sohn et al 2007; Tomee et al 1998; Wong et al 2006). Most of the lung studies have challenged epithelial cells with specific allergens (mostly group 1) or whole extract of D. pteronyssinus .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a mechanism for dust mite–induced atopic dermatitis and suggests that avoiding skin contact with house dust mites may decrease mite-induced inflammation. 125 …”
Section: Health Effectsmentioning
confidence: 99%
“…Previous studies found that D. farinae extracts contained more endotoxin than D. pteronyssinus [1,2,3]. Mite extracts also contain molecules that induce cytokine release by cultured dermal fibroblasts, epidermal keratinocytes, endothelial cells of the dermal microvasculature, and lung epithelial cells and thereby may influence inflammation in the skin and respiratory system [4,5,6,7,8,9]. Thus, molecules in mite extracts may influence the course of allergic reactions.…”
Section: Introductionmentioning
confidence: 99%